Effect of Over-Pruning and NPKMg Fertilization on the Yield Components and Productivity of Oil Palm (Elaeis guineensis Jacq.) - Muhammad Wildan Ar-Rosyad; Amrul Khoiri; Nelvia (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effects of N, P, K, and Mg fertilization on improving growth parameters and productivity of oil palm plants subjected to over-pruning. The experiment was conducted using a completely randomized split-plot design with two factors: pruning treatment as the main factor and N, P, K, and Mg fertilization as the second factor. The observed parameters included the number of female inflorescences, number of male inflorescences, sex ratio, number of fruit bunches, bunch weight, fresh fruit weight, fresh fruit volume, mesocarp thickness, and fruit lipid content. The data obtained were statistically analyzed using analysis of variance, followed by Duncan’s New Multiple Range Test (DNMRT) at the 5% significance level. The results showed that the P1 treatment, representing normal pruning, combined with the N3 fertilization treatment improved several growth and productivity parameters, including the number of female inflorescences (5.02), number of fruit bunches (5.83), sex ratio (60.12%), fruit bunch weight (20.40 kg), fresh fruit weight (12.43 g), mesocarp thickness (3.93 mm), fresh fruit volume (12.59 mL), and fresh fruit lipid content (20.21%). In contrast, over-pruning tended to increase the number of male inflorescences (4.00), indicating a decline in the reproductive performance of the plants. In conclusion, normal pruning and the application of N, P, K, and Mg fertilizers significantly improved the growth and productivity of oil palm plants affected by over-pruning, particularly by increasing the number of female inflorescences, number of fruit bunches, sex ratio, fruit bunch weight, fresh fruit weight, mesocarp thickness, fresh fruit volume, and fresh fruit lipid content.